Boa colocação das equações de Navier-Stokes em espaços de Morrey - Amaral, Sabrina Suelen [UNESP] (2017)
In this work we will analyze the Navier-Stokes equations in R^n, (n≤3) and we will show global well-posedness, when the initial velocity belongs to the Morrey space and with a sufficiently small norm. We will also show that if the initial data is a homogeneous function of degree -1, then the mild solutions are self-similar. Moreover, we will present an asymptotic stability result of the mild solutions.